A New Kind of Biomedical Ti–Mn–Nb Alloy. Issue 7 (22nd February 2023) - Zhang, H.; Wang, C. P.; Pyczak, F.; Ebel, T.; Liu, X. J.
Abstract : Titanium and its alloys are widely used as implant biomaterials due to their well mechanical properties and biological compatibilities. Nb and Mn are well‐known alloying elements with biological potential. Herein, the Ti–Mn–Nb phase equilibria at 900 °C (Ti‐rich region) is determined and published. According to the β single‐phase field in this phase diagram (at 900 °C), Ti– x Mn– y Nb ( x  = 4, 10, 16; y  = 2, 8, 14, at%) alloys are selected and fabricated which are suited for solution heat treatment. The Ti–Mn–Nb alloys are investigated by optical microscopy (OM), X‐ray diffraction (XRD), and mechanical testing. A unique diffraction pattern (interpreted as occurrence of a transition phase) is observed by transmission electron microscopy (TEM) in Ti–10Mn–2Nb. In the in vitro evaluation, the human osteoblasts (MG63) adhere well and proliferate on the surface of Ti– x Mn– y Nb ( x  = 4, 10; y  = 2, 8, 14, at%). According to cell culture experiments, the alloys are nontoxic to human osteosarcoma cells in comparison with pure titanium. Based on a performed screening study, different titanium alloys Ti–4Mn– y Nb ( y  = 2, 8, 14) appear as the biomaterial with the highest potential around 700 MPa ultimate tensile strength and 9–10% elongation. Abstract : The Ti–Mn–Nb phase equilibria diagram at 900 °C (Ti‐rich region) is determined. A unique diffraction pattern has been observed by transmission electron microscope. The alloys are nontoxic to human osteosarcoma cells in comparison with pure titanium. Ti–4Mn– y Nb ( y  = 2, 8, 14) alloys have the potential to be implant biomaterials exhibiting a superior combination of properties compared to established materials.